Analysis of Wifi Network Security with Packet Sniffing Technique at RRI Bengkulu Public Broadcasting Institution - Yulia Astuti; Hari Aspriyono; Ricky Zulfiandry (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The problem of wireless technology offers a variety of convenience, freedom and high flexibility. Wireless technology has quite a lot of advantages compared to existing wired technology, including easy access to data communication and internet access in any position as long as it is still in a wireless network. The method used is the Network Development Life Cycle (NDLC) method, a cycle of network design stages that can guide a network design, which depends on the size of the project to be implemented and the purpose of the project. Wireless security testing uses airodump-ng as an attack medium and security analysis uses wireless packet sniffing method which will be described in the wireshak application. Packet sniffing is a process for capturing packets passing through a computer network. Based on the analysis and attack experiments carried out, it still needs improvement, this is with the airodump-ng application detecting nearby WiFi and packet sniffing attacks can display usernames and passwords using the wireshak application.